VIRTUAL LEARNING AMIDST COVID-19 OUTBREAK: THE CHALLENGES IN LANGUAGE LEARNING - Dita Rizki Anggraini (Global Expert: Jurnal Bahasa dan Sastra, 2022)
The outbreak of COVID-19 has put the universe into a big changes. Most sectors of life including education has to be adjusted for the sake of everybody’s safety. Language learning, which ideally needs a lot of interactions, should be held virtually. This sudden shift may cause several intervening factors which influence the success of it. This study was aimed at discussing the factors that may challenge the language learning during the virtual learning mode amidst the COVID-19. After studying some research about this issue, several factors namely lack of internet access, poor comprehension, poor interaction, overload tasks, insufficient infrastructure support, environmental distraction, and lack of motivation are found to be the challenges in implementing a successful virtual language learning amidst the outbreak.